Pengaruh Tingkat Kesehatan Bank dengan Metode RGEC terhadap Profitabilitas pada Bank Umum Konvensional yang Terdaftar di Bursa Efek Indonesia (BEI) Periode 2022-2025 - Lisa Sari; Puji Astuti; Badrus Zaman (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study aims to analyze the effect of bank soundness using the RGEC method (Risk Profile, Good Corporate Governance, Earnings, and Capital) on profitability in Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX) during 2022–2025. Risk Profile is proxied by Non-Performing Loan (NPL), Good Corporate Governance (GCG) is measured using composite self-assessment scores, Earnings is proxied by Net Interest Margin (NIM), Capital is proxied by Capital Adequacy Ratio (CAR), and profitability is proxied by Return on Assets (ROA). This research applies a quantitative causal approach using secondary data from annual financial reports. The sample consists of 18 banks selected through purposive sampling, resulting in 72 observations. Data were analyzed using multiple linear regression with IBM SPSS version 25. The results indicate that NPL and GCG have a significant negative effect on ROA, while NIM has a significant positive effect on ROA. CAR does not have a significant effect on ROA. Simultaneously, all independent variables significantly influence ROA. These findings suggest that bank soundness measured by RGEC plays an important role in determining profitability. Therefore, banks should maintain credit risk quality, strengthen corporate governance, and optimize interest income to support sustainable performance and long-term financial stability. This study also provides practical implications for regulators and investors in assessing bank performance and risk management effectiveness, while encouraging consistent policy implementation and improved financial resilience within the banking sector in Indonesia to ensure sustainable economic growth and stability in the future periods ahead overall and across different market conditions consistently.